Validation of an instrument for measuring the technology acceptance of a virtual learning environment - Santana-Mancilla, Pedro César; Montesinos-López, Osval Antonio; Garcia-Ruiz, Miguel Angel; Contreras-Castillo, Juan José; Gaytan-Lugo, Laura Sanely (Acta Universitaria, 2019)
Virtual Learning Environments (VLE) provide platforms to make online education more convenient and affordable for learners. Although VLE are currently in great demand, their acceptance needs to be assessed. In this research, an instrument that measures the technology acceptance of a VLE is validated by applying a confirmatory factor analysis on 15 items and five factors. Results show that the overall fit of the model was satisfactory and that all correlations between the latent factors were higher than 0.48. It was found that the assessment of technology acceptance is very important, because the VLE’s success depends largely on the favorable reception of professors, researchers, and educational leaders.